Establishment of a nomogram that predicts the risk of heart failure in hemodialysis patients - Jie Luo; Zhangru Rui; Yun He; Hui Li; Yang Yuan; Wenhong Li (American Heart Journal Plus)
Chronic kidney disease (CKD) is expected to become the fifth leading cause of death globally by 2040. Cardiovascular disease (CVD), particularly heart failure (HF), is a severe complication in CKD patients on hemodialysis. This study aimed to develop a nomogram to predict the risk of heart failure hospitalization in hemodialysis patients, providing a valuable tool for clinical decision-making. We retrospectively analyzed data from 196 patients at Kunming Yanan Hospital's hemodialysis center, including demographic, dialysis-related, and laboratory information. Significant HF predictors identified through univariate and multivariate logistic regression were age, diabetes, dialysis duration, left ventricular mass index (LVMI), albumin (ALB), and ejection fraction (EF). These predictors formed the basis of the nomogram, which demonstrated good discrimination (AUC = 0.728) and calibration (Hosmer-Lemeshow test, P = 0.463). Decision curve analysis confirmed the nomogram's clinical utility across various threshold probabilities. This study's findings can help clinicians identify high-risk patients, improving management strategies and potentially reducing HF-related hospitalizations in the hemodialysis population.